E2F1 suppresses cardiac neovascularization by down-regulating VEGF and PlGF expression. (23rd October 2014) - Wu, Min; Zhou, Junlan; Cheng, Min; Boriboun, Chan; Biyashev, Dauren; Wang, Hong; Mackie, Alexander; Thorne, Tina; Chou, Jonathan; Wu, Yiping; Chen, Zhishui; Liu, Qinghua; et al.
Abstract: Aims: The E2F transcription factors are best characterized for their roles in cell-cycle regulation, cell growth, and cell death. Here we investigated the potential role of E2F1 in cardiac neovascularization. Methods and results: We induced myocardial infarction (MI) by ligating the left anterior descending artery in wild-type (WT) and E2F1 −/− mice. E2F1 −/− mice demonstrated a significantly better cardiac function and smaller infarct sizes than WT mice. At infarct border zone, capillary density and endothelial cell (EC) proliferation were greater, apoptotic ECs were fewer, levels of VEGF and placental growth factor (PlGF) were higher, and p53 level was lower in E2F1 −/− than in WT mice. Blockade of VEGF receptor 2 (VEGFR2) signalling with the selective inhibitor SU5416 or with the VEGFR2-blocking antibody DC101 abolished the differences between E2F1 −/− mice and WT mice in cardiac function, infarct size, capillary density, EC proliferation, and EC apoptosis. In vitro, hypoxia-induced VEGF and PlGF up-regulation was significantly greater in E2F1 −/− than in WT cardiac fibroblasts, and E2F1 overexpression suppressed PlGF up-regulation in both WT and p53 −/− cells; however, VEGF up-regulation was suppressed only in WT cells. E2F1 interacted with and stabilized p53 under hypoxic conditions, and both E2F1 : p53 binding and the E2F1-induced suppression of VEGF promoter activity were absent in cells that expressed an N-terminally truncated E2F1 mutant. Conclusion: E2F1 limits cardiac neovascularization and functional recovery after MI by suppressing VEGF and PlGF up-regulation through p53-dependent and -independent mechanisms, respectively.